Intelligent computing theories and application : 13th International Conference, ICIC 2017, Liverpool, UK, August 7-10, 2017, Proceedings.: 13th International Conference, ICIC 2017, Liverpool, UK, August 7-10, 2017, Proceedings. Part I (2017) - Unknown
No abstract available